Moral values in the Holy Qur'an - Zedan, A.M.; Alqarni, K.A. (Islamic Cultural Centre, 2016)
The concept of moral values is a significant feature of the ideal Muslim society but most contemporary so-called Islamic communities are devoid of it. This research seeks to identify those values and suggest their proper application in search of a panacea for the appalling situation through library research using both inductive and deductive methodologies. Its findings are that solving the problem of enhancing Islamic social norms lies in Surat Al-Furqan of Allah's book of guidance, the Qur'an. It concludes with the significance of attracting good companions and abandoning bad ones to enhance moral values in Muslim society.